Dynamical tuning of energy transfer efficiency on a graphene monolayer - Bradley, Louise (My University, 2015)
In this contribution we present a theoretical investigation of the energy transfer efficiency between quantum systems placed in proximity of a monolayer of conducting graphene. We calculate the spontaneous emission rate of a quantum system and the energy transfer rate between a donor-acceptor pair, and thus the energy transfer efficiency, using a Green's tensor formalism. The direct interaction between the donor and acceptor dominates when they are close to each other, but is modified from its free-space behavior due to the presence of the graphene monolayer and its interaction with the donor and acceptor. We report on a very large influence of the graphene monolayer on the energy transfer efficiency due to both the Förster mechanism and the propagating graphene plasmon mode. In particular, the Förster radius R0 is modified from its free-space value of 20 nm and can reach values of 120 nm when close to a graphene monolayer. As the donor-acceptor separation is increased, their direct interaction is overshadowed by the interaction via the surface plasmon mode. Due to the large propagation length of the surface plasmon mode on graphene, an energy transfer efficiency as high as 50% can still be achieved for distances as large as 300 nm. The interaction via the surface plasmon mode is tunable via the doping of the graphene monolayer and the surface plasmon channel can also be switched off this way.
PUBLISHED
Keywords: graphene